Oil-In-Water Microemulsion Liquid Chromatography. Issue 2 (2nd April 2020) - Peris-García, Ester; Pankajkumar-Patel, Nikita; Ruiz-Angel, María José; Carda-Broch, Samuel; García-Alvarez-Coque, María Celia
Abstract : Oil-in-water microemulsions (O/W MEs) are obtained spontaneously by mixing two immiscible liquids (water and oil) in the presence of a surfactant. A co-surfactant is also often needed for ME stabilization. The surfactant provides a microstructure with a definite boundary between oil and water phases. O/W MEs are used as mobile phases in a chromatographic mode known as microemulsion liquid chromatography (MELC). One of the main appeals of O/W MEs is the ability to solubilize compounds in a wide range of polarities, from polar to hydrophobic. The solubilizing effect on sample matrices is also noteworthy. The dual behavior of O/W MEs offers unique selectivity and reduced retention times, with equivalent or superior efficiency compared to conventional reversed-phase liquid chromatography, giving rise to successful isocratic separations. The complex nature of MELC mobile phases allows numerous composition options (type and concentration of surfactant, oil and co-surfactant) that lead to good separation performance, when compared to other chromatographic modes. A thorough revision of the main topics concerning MELC, such as nature and properties of O/W MEs, mechanism of retention, selectivity and diverse aspects related to the experimental practice for the determination of drugs in clinical and pharmaceutical samples, is presented.